2023
DOI: 10.1038/s41467-022-34256-y
|View full text |Cite
|
Sign up to set email alerts
|

High-depth sequencing characterization of viral dynamics across tissues in fatal COVID-19 reveals compartmentalized infection

Abstract: SARS-CoV-2 distribution and circulation dynamics are not well understood due to challenges in assessing genomic data from tissue samples. We develop experimental and computational workflows for high-depth viral sequencing and high-resolution genomic analyses from formalin-fixed, paraffin-embedded tissues and apply them to 120 specimens from six subjects with fatal COVID-19. To varying degrees, viral RNA is present in extrapulmonary tissues from all subjects. The majority of the 180 viral variants identified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…While our studies here were limited to the brain, we hypothesize that tissue-specific patterns of viral diversity may develop across other anatomical sites and contribute to the population structure of the viral quasispecies in an infected host. Indeed, sequencing of SARS-CoV-2 from heart tissue found an overrepresentation of the Spike Q675H mutation, which has been suggested to enhance furin cleavage 50 , 51 . On the other hand, the immune privileged status of the CNS may facilitate longer infection time courses in those tissues, which would enable a higher degree of genetic diversification specifically in that compartment.…”
Section: Discussionmentioning
confidence: 99%
“…While our studies here were limited to the brain, we hypothesize that tissue-specific patterns of viral diversity may develop across other anatomical sites and contribute to the population structure of the viral quasispecies in an infected host. Indeed, sequencing of SARS-CoV-2 from heart tissue found an overrepresentation of the Spike Q675H mutation, which has been suggested to enhance furin cleavage 50 , 51 . On the other hand, the immune privileged status of the CNS may facilitate longer infection time courses in those tissues, which would enable a higher degree of genetic diversification specifically in that compartment.…”
Section: Discussionmentioning
confidence: 99%
“…performed next-generation sequencing on 120 specimens using formalin-fixed, paraffin-embedded tissues from six patients who experienced fatal COVID-19. 126 They reported that a majority of the 180 SARS-CoV-2 mutational patterns identified in these patients were unique to given tissue samples, indicating compartmentalized infections in extrapulmonary sites. The spike protein amino acid substitution Q675H, present as a minority mutation in heart tissue, was not circulating at the time the patient died but was later detected in the consensus genomes from several SARS-CoV-2 lineages.…”
Section: Quasispecies For Sars-cov-2mentioning
confidence: 94%
“…Also, an association of five mutations with the upper respiratory tract (U2055G, U2058G, U2060G, U2100G, and A3483S) and four mutations with the lower respiratory tract (C212A, A3005U, C3485U/G, and A3596G/U) was found. Finally, Normandin et al performed next‐generation sequencing on 120 specimens using formalin‐fixed, paraffin‐embedded tissues from six patients who experienced fatal COVID‐19 126 . They reported that a majority of the 180 SARS‐CoV‐2 mutational patterns identified in these patients were unique to given tissue samples, indicating compartmentalized infections in extrapulmonary sites.…”
Section: The Case For Covid‐19 Including Sars‐cov‐2mentioning
confidence: 99%
“…Transcriptomic approaches in particular enable quantification of host transcripts and pathogen sequences, shedding light on relevant host factors, tissue pathologies, cellular targets of infection, and emerging genetic variation. 8 , 9 , 10 , 11 Comparative analyses of these signals between pathogens and populations can identify pathogen-agnostic and pathogen-specific responses, thereby indicating pathways of potential evolutionary and therapeutic significance. 12 Despite the important roles genomics and transcriptomics have played in our understanding of diseases, including coronavirus disease 2019 (COVID-19), 8 , 9 , 10 , 11 many severe viral threats have not been studied as extensively, in particular high-containment pathogens.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 Comparative analyses of these signals between pathogens and populations can identify pathogen-agnostic and pathogen-specific responses, thereby indicating pathways of potential evolutionary and therapeutic significance. 12 Despite the important roles genomics and transcriptomics have played in our understanding of diseases, including coronavirus disease 2019 (COVID-19), 8 , 9 , 10 , 11 many severe viral threats have not been studied as extensively, in particular high-containment pathogens. Thus, there is a need for improved datasets and analytical methods integrating transcriptomics data to build a comprehensive understanding of molecular factors involved in diverse pathologies.…”
Section: Introductionmentioning
confidence: 99%